2019
DOI: 10.1016/j.triboint.2019.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Tribological performance of hygrothermally aged UHMWPE hybrid composites

Abstract: (LTU) as part of the TRIBOS program-Joint European Master in Tribology of Surfaces and Interfaces. I would like to thank everyone involved in the organization of the TRIBOS for making this opportunity possible by funding, guiding and supporting throughout this 2-year journey. Thanks to Professor Nazanin Emami and Hari Shankar for the guidance, support, discussions, and patience throughout the work. Also, I would like to thank all the TRIBOS colleagues and TRIBOLAB staff for the help and friendship. Finally, I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 64 publications
1
15
0
Order By: Relevance
“…First, considering the reliability of outdoor exposure and UV aging, UHMWPE was selected as the raw material for the NCF, which only has the simplest methylene structure without polar bonds, resulting in superior chemical resistance . It has been demonstrated that the composite fabric hardly absorbs UV light, and there is no significant effect on the Fourier transform infrared (FTIR) spectra for the UHMWPE aged at 80 °C and 120 days . Moreover, we performed several tests on the proposed NCF, including the hydrophilicity, mechanical strength, and thermostability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, considering the reliability of outdoor exposure and UV aging, UHMWPE was selected as the raw material for the NCF, which only has the simplest methylene structure without polar bonds, resulting in superior chemical resistance . It has been demonstrated that the composite fabric hardly absorbs UV light, and there is no significant effect on the Fourier transform infrared (FTIR) spectra for the UHMWPE aged at 80 °C and 120 days . Moreover, we performed several tests on the proposed NCF, including the hydrophilicity, mechanical strength, and thermostability.…”
Section: Resultsmentioning
confidence: 99%
“…49 It has been demonstrated that the composite fabric hardly absorbs UV light, 44 and there is no significant effect on the Fourier transform infrared (FTIR) spectra for the UHMWPE aged at 80 °C and 120 days. 50 Moreover, we performed several tests on the proposed NCF, including the hydrophilicity, mechanical strength, and thermostability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Hygrothermal ageing experiments on short glass fiber reinforced polyamide 66 (PA66), treated oil palm fibre reinforced polyester (T-OPRP), and ultra high molecular weight polyethylene (UHMWPE) resulted in an increased dynamic friction in the first two cases, while causing an insignificant change in that of the third. Furthermore, the results of wear resistance measurements indicated dependency on the reinforcement rate in the first case, and a notable reduction and inconsiderable variation in the last two cases, respectively [14][15][16]. To the best of the authors' knowledge, there is no published research on the tribological evaluation of PTFE and its composites considering the effects of hygrothermal ageing.…”
Section: Introductionmentioning
confidence: 95%
“…Nano-filling modification is a common method to improve the properties of polymers. [15][16][17][18][19][20] Among the many fillers, carbon nanofibers (CNF) is a very attractive nano-filler for polymer composites because of their strong chemical stability, high temperature resistance, corrosion resistance, high mechanical properties, and low cost. [21][22][23] Sui [24] studied the effects of untreated and pretreated carbon nanofibers on the mechanical and tribological properties of UHMWPE and high density polyethylene (HDPE) composites.…”
Section: Introductionmentioning
confidence: 99%